1976
DOI: 10.1111/j.1600-0528.1976.tb00981.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a dental education program on oral cleanliness of schoolchildren in Israel

Abstract: The purpose of this study was to examine the effectiveness of a dental health education program providing dental health information and toothbrushing instruction on oral cleanliness. Two methods of instruction, individual and group instruction, are presented in this study. The plaque situation was assessed in a group of 175 children, 11-14 years of age, by the Patient Hygiene Performance (PHP) method at the beginning of the study and at 1, 2, and 12 months. It was found that immediately after instruction the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
3

Year Published

1991
1991
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
2
11
3
Order By: Relevance
“…Another important consideration is that there was a tendency of relapse in knowledge and/or oral hygiene with time 17,35–38 . Although there were follow‐up studies where the maintenance of improved oral hygiene in adolescents after a longer period was shown 18,28,39,40 , these findings cannot be defined as an actual long‐term success as the results were achieved in conjunction with the reinforcement programmes. Only one study reported a period of 44 weeks with improved oral hygiene status in the absence of any repeated interventions 35 .…”
Section: Resultsmentioning
confidence: 99%
“…Another important consideration is that there was a tendency of relapse in knowledge and/or oral hygiene with time 17,35–38 . Although there were follow‐up studies where the maintenance of improved oral hygiene in adolescents after a longer period was shown 18,28,39,40 , these findings cannot be defined as an actual long‐term success as the results were achieved in conjunction with the reinforcement programmes. Only one study reported a period of 44 weeks with improved oral hygiene status in the absence of any repeated interventions 35 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies analysing plaque levels after oral hygiene in young adults are rare (Anaise & Zilkah 1976). Most available studies assess plaque prior to oral hygiene and thereby confound patients' motivation for daily oral hygiene and their ability to remove plaque (Crawford et al 1975, Albandar et al 1994, D'Cruz & Aradhya 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Our review confirmed the equivocal nature of dental health education programs, with methodological problems such as poor study objectives (3-61, little detail of program activities (7-18), and small sample sizes (9,19-25). Subject testing frequently focused on short-term scores (20,21,2631), with poor statistical tests (5,32) and lack of examiner calibration or reliability measure (19,33-38). So, although the studies detail the various types of interventions used in dental health education programs, there is no clear conclusion on the efficacy or effectiveness of such programs.…”
mentioning
confidence: 99%